(untitled) (Research, Society and Development, 2022)
Objective: to present the methodological steps of a scope review protocol to map the available evidence about care management actions for patients with COVID-19 hospitalized in wards. Method: this is a scope review protocol developed according to the methodology proposed by the JBI manual and the PRISMA-ScR Checklist. The PCC acromion strategy was used to formulate the research question, and studies that answer the question “What are the care management actions carried out by the nurse for the patient with COVID-19, hospitalized in the ward?”, to be searched in MEDLINE electronic databases via PubMed, LILACS, Scopus, Embase, Web of Science, Cochrane, CINAHL, BVS and Google Scholar. The selection of studies will occur independently by two researchers, using an instrument built by them in the Microsoft Office Excel Online program to assist in the synthesis and extraction of data that will be compiled into figures and flowcharts, followed by discussion and mention of practical implications. for the role of nurses in care management. Final considerations: The findings may support the assistance to patients with other pathologies characterized by respiratory syndrome.